TO WHAT EXTENT IS MATH HELPFUL? EXAMPLES OF APPLIED MATH: FROM FRACTIONS TO RESOURCE MANAGEMENT IN AN ORGANIZATION - Luminita Catana (National Centre for Policy and Evaluation in Education, 2015)
Resource allocation is an important issue for managers and for the members of a team, and its fair solution is not possible without math. From simple fractions to the more complex mathematical models is nevertheless a long way. A general observation is that, usually, the resources are limited, or they have an accumulation rate slower than the people's demands or needs, which causes dissatisfaction and even conflicts among the group members. This article addresses this issue with the use of mathematical support. Mathematics tells us that if we choose resource allocations strategies which allow every person to be satisfied with the resources he/she receives, or if the resources are shared in a "right" way, the dissatisfaction will be less frequent and with a lower intensity. This article presents, in an accessible way, some mathematical models which could be used as practical applications in entrepreneurial education or math classes in high-school, that give students a base for further discussions and learning.